(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The real estate market is one of the most important elements of a modern econo-my. Variable that could potentially have vital importance in the shaping of the situation on the market is the interest rate. This paper discusses the problem of the impact of interest rates on the real estate market. The description used the Granger causality test and harmonic analysis.